Expression of MIP-1α (CCL3) by a Recombinant Rabies Virus Enhances Its Immunogenicity by Inducing Innate Immunity and Recruiting Dendritic Cells and B Cells - Zhao, Ling (American Society for Microbiology (ASM), 2010)
Previously, we showed that overexpression of MIP-1α in mouse brain further decreased rabies virus (RABV) pathogenicity (L. Zhao, H. Toriumi, Y. Kuang, H. Chen, and Z. F. Fu, J. Virol., 83:11808-11818, 2009). In the present study, the immunogenicity of recombinant RABV expressing MIP-1α (rHEP-MIP1α) was determined. It was found that intramuscular immunization of BALB/c mice with rHEP-MIP1α resulted in a higher level of expression of MIP-1α at the site of inoculation, increased recruitment of dendritic cells (DCs) and mature B cells into the draining lymph nodes and the peripheral blood, and higher virus-neutralizing antibody titers than immunization with the parent rHEP and recombinant RABVs expressing RANTES (CCL5) or IP-10 (CXCL10). Our data thus demonstrate that expression of MIP-1α not only reduces viral pathogenicity but also enhances immunogenicity by recruiting DCs and B cells to the site of immunization, the lymph nodes, and the blood.